2017
DOI: 10.1136/bmjopen-2016-013206
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the prognostic values of inflammation markers in patients with acute pancreatitis: a retrospective cohort study

Abstract: ObjectivesInflammation-based prognostic markers (neutrophil–lymphocyte ratio (NLR), prognostic nutritional index (PNI), red cell distribution width (RDW) and lymphocyte–monocyte ratio (LMR)) are associated with overall survival in some diseases. This study assessed their prognostic value in mortality and severity in acute pancreatitis (AP).DesignA retrospective cohort study.SettingPatients with AP were recruited from the emergency department at our hospital.ParticipantsA total of 359 patients with AP (31 non-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
77
3
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(88 citation statements)
references
References 35 publications
7
77
3
1
Order By: Relevance
“…They found a significant association between NLR and the duration of intensive care, the risk of developing persistent organ failure, and mortality. Li et al performed a single‐center retrospective study with 359 AP patients and determined NLR to be the most reliable marker of overall survival. Jeon et al performed a retrospective study with 490 AP patients and established a relationship between NLR, AP severity, and the development of multiorgan failure.…”
Section: Discussionmentioning
confidence: 99%
“…They found a significant association between NLR and the duration of intensive care, the risk of developing persistent organ failure, and mortality. Li et al performed a single‐center retrospective study with 359 AP patients and determined NLR to be the most reliable marker of overall survival. Jeon et al performed a retrospective study with 490 AP patients and established a relationship between NLR, AP severity, and the development of multiorgan failure.…”
Section: Discussionmentioning
confidence: 99%
“…There is no reliable predictor or a consensus on the preference of use of one or the other systems in case of persistent organ failure. Despite the evidence, no studies have reported a direct relationship between prognostic and mortality markers [67]. On the basis of expert opinions, it is possible to state that despite the simplicity of Ranson's criteria, its convenience to remember, and the wide availability of tests to perform in any laboratory, this prediction rule is full of uncertainties, uncomfortable and confusing as the criteria vary according to the biliary etiology, and instead of evaluating 11 factors, it sometimes evaluates 22.…”
Section: Scoring Systemsmentioning
confidence: 98%
“…It also predicts the duration of hospital stay. It is not useful in determining the severity of organ failure or the number of failed organs [67].…”
Section: Scoring Systemsmentioning
confidence: 99%
“…Predicts the occurrence of early organ failure with similar or greater precision to SIRS, Bisap and Balthazar, and duration of the hospital stay. It is not useful to differentiate the severity of organ failure, and the number of organs failed [69].…”
Section: Scoring Systemsmentioning
confidence: 99%
“…There is no reliable predictor or consensus on the preference of use of one or the other of the systems for persistent organ failure. Despite the evidence, there are no studies with a direct relationship between prognostic and mortality markers [69]. Based on expert opinions we can say that Ranson's criteria although simple, easy to remember and widely available tests to perform them in any laboratory, it is filled with uncertainties, uncomfortable and confusing as they vary according to the biliary etiology, and instead of evaluating 11 factors become 22.…”
Section: Scoring Systemsmentioning
confidence: 99%